Quality of Life and Poor Oral Health: A Comparison of Postmenopausal Women - Kristin A. Williams; Hebba Shamia; Christine DeBaz; Leena Palomo (Dentistry Journal, 2016)
Inter-relationships between traditional dental variables are becoming more evident in far reaching aspects of life, such as psychosocial interaction, self-esteem, overall health and even occupational performance. This study compares quality of life (QoL) in postmenopausal women (PMW) with poor oral health (POH) with QoL in PMW with good oral health. A total of 200 randomly recruited PMW received a dental evaluation and completed the Utian Quality of Life Survey. The participants were divided into POH and healthy groups based on a dental exam. Mean scores were calculated for each QoL item, domain and the overall summary score. For each of the four parameters for periodontitis diagnosis, periodontitis b s patients’ QoL outcomes were compared to those of healthy patients using a T-test with a threshold of significance at p < 0.05. QoL in all fields measured was significantly poorer in the POH patients compared to the healthy patients: occupational score (19.95 ± 5.35 vs. 27.56 ± 6.13), health score (18.02 ± 8.23 vs. 26.59 ± 6.45), emotional score (15.68 ± 10.22 vs. 21.15 ± 9.15), sexual score (6.2 ± 5.98 vs. 10.02 ± 5.35), and total score (60.21 ± 25.85 vs. 84.26 ± 22.35). This study finds that PMW with POH report significantly poorer quality of life. Clinicians caring for PMW should be aware that oral health impacts QoL and make appropriate referral decisions for patients’ dental care.